2022
DOI: 10.1007/s10935-022-00697-w
|View full text |Cite
|
Sign up to set email alerts
|

Cost–Benefit Analysis of Human Papillomavirus Vaccine in Iran

Abstract: Background: Despite increasing global attention to the national human papillomavirus (HPV) immunization program, this program is controversial in Iran. Evidence indicate that HPV vaccination is not cost-effective in Iran. Using cost-effectiveness analysis for decision-making about public health interventions such as vaccination is debated, because its potential bene ts may not t this framework. Our objective was to evaluate economic effects of HPV vaccination by cost-bene t analysis (CBA). In this case, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Some studies reported that the quadrivalent vaccine has a higher cost-benefit ratio compared to the bivalent vaccine in Iran. However, it is important to consider other factors, such as vaccine efficacy and coverage rates, when making decisions about vaccination strategies in the country ( 48 , 77 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported that the quadrivalent vaccine has a higher cost-benefit ratio compared to the bivalent vaccine in Iran. However, it is important to consider other factors, such as vaccine efficacy and coverage rates, when making decisions about vaccination strategies in the country ( 48 , 77 ).…”
Section: Resultsmentioning
confidence: 99%
“…We used the health care costs of treated and untreated persons in the CC states, which involved costs of hospitalization, medicaments, and CC treatments in Iran. Costs of vaccination consist of a two-dose quadrivalent vaccination and administration costs and was set at USD 152, which included an assumed USD 1 for administration [22]. Total health care treatment costs were estimated by dividing the total costs of CC treatment in Iran by the number of treated CC cases, and was set at USD 26,850 [22].…”
Section: Costsmentioning
confidence: 99%
“…Costs of vaccination consist of a two-dose quadrivalent vaccination and administration costs and was set at USD 152, which included an assumed USD 1 for administration [22]. Total health care treatment costs were estimated by dividing the total costs of CC treatment in Iran by the number of treated CC cases, and was set at USD 26,850 [22]. Costs were discounted with a rate of 3.5% [21].…”
Section: Costsmentioning
confidence: 99%
See 1 more Smart Citation